Molecular characterization of Enterotoxigenic Escherichia coli isolates harboring genetic elements mediating multiple-drug resistance - KOHANSAL, M.; NAJAFI, A.; VIDAL, R. (Journal of the Hellenic Veterinary Medical Society, 2020)
Intensive antibiotics’ use in the management of the disease in neonate calves, a major economic concern in bovine industry, is one of the contributors to high levels of antibiotic resistance of pathogenic bacteria. The objective of this study was to investigate the antibiotic resistance patterns and the frequency of integrons classes among Enterotoxigenic Escherichia coli (ETEC) strains isolated from neonatal calf diarrhea (NCD) in South of Iran. 412 recto-anal mucosal swabs from diarrheic calves were analyzed by biochemical fingerprinting and for virulence genes by polymerase chain reaction (PCR). The isolates were examined for their susceptibility to a panel of 8 antibacterial agents using the Kirby-Bauer disc diffusion method. Finally, the frequency of integron classes was detected in multi-drug resistant (MDR) strains by polymerase chain reaction restriction fragment length polymorphism (PCR- RFLP). 194 out of 412 (47.09%) diarrheic fecal samples harbored E. coli and 35 (18%) of them were identified as ETEC. The drug susceptibility test showed that all isolates were resistant to erythromycin, penicillin and trimethoprim/sulfamethoxazole and more than 80% were resistant to ampicillin and chloramphenicol. All isolates were MDR. 17 out of 35 (48.57%) isolates were identified possessed class 1 integron. High prevalence of class 1 integron in ETEC isolates was mainly associated with multidrug resistance. Cefixime was the most effective antibiotic in vitro.